Региональная идентичность Донбасса: генезис и тенденции развития в условиях общественной трансформации - Коржов, Г. (Социология: теория, методы, маркетинг, 2006)
The article analyzes processes of regional identification in Donbass. The major factors determining the increase in the feelings of belonging to an imagined community based on the commonality of territory are identified. The shared socio- cultural experience,similar value attitudes, and way of living are the most significant among them. One may conclude that the rise of regional identity in Donbass was concomitant with the consolidation of the oligarchic model of government and the patron client model of social organization hinged upon unequal distribution of power and resources.